2 A DIGEST OF THE LAWS OF TEXAS: CONTAINING THE LAWS IN FORCE, AND THE REPEALED LAWS ON WHICH RIGHTS REST, FROM 1754 TO 1874, at 1323 (George W. Paschal ed., 4th ed. 1874). Art. 6511 - (:unkn) unknown (General Publisher, 1870)
Prohibited the carry of any bowie-knife, dirk, butcher-knife, or fire-arms, including any six-shooter, gun, or pistol into any church, religious assembly, any school-room or other place where persons are assembled for educational, literary, or sceintific purposes, or into a ball-room, social party, or other social gathering, composed of ladies and gentlemen, or to any election precinct on the day or days of any election, where any portion of the people of this state are collected to vote at any election, or to any other place where people may be assembled to muster, or to perform any other public duty, or any other public assembly.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES